2002
DOI: 10.1001/archinte.162.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Related Barriers to the Effective Management of Uncontrolled Hypertension

Abstract: Our findings suggest that an important reason why physicians do not treat hypertension more aggressively is that they are willing to accept an elevated systolic BP in their patients. This has an important impact on public health because of the positive association between systolic BP and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
294
2
13

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(328 citation statements)
references
References 53 publications
19
294
2
13
Order By: Relevance
“…There are several common reasons for therapeutic ineffectiveness in these groups that might be remedied by changing improvement targets 40. For instance, failure to change or increase therapy for patients who are not at goal (“therapeutic inertia”)41, 42 can be addressed by leveraging EHRs to implement treatment algorithms and protocols,16, 28, 38 utilizing clinical decision support tools embedded within EHRs including a 2‐week follow‐up process and patient reminders,19 and changes in team care 43, 44, 45, 46. Treatment‐resistant hypertension is related to age, patient factors, and medical causes of secondary hypertension47 and can be explored by implementing streamlined referral pathways35 and pushing EHR alerts to providers when the BP is elevated 30…”
Section: Discussionmentioning
confidence: 99%
“…There are several common reasons for therapeutic ineffectiveness in these groups that might be remedied by changing improvement targets 40. For instance, failure to change or increase therapy for patients who are not at goal (“therapeutic inertia”)41, 42 can be addressed by leveraging EHRs to implement treatment algorithms and protocols,16, 28, 38 utilizing clinical decision support tools embedded within EHRs including a 2‐week follow‐up process and patient reminders,19 and changes in team care 43, 44, 45, 46. Treatment‐resistant hypertension is related to age, patient factors, and medical causes of secondary hypertension47 and can be explored by implementing streamlined referral pathways35 and pushing EHR alerts to providers when the BP is elevated 30…”
Section: Discussionmentioning
confidence: 99%
“…The difference in achieving the goal for SBP or DBP for the male population was less remarkable. A recently published descriptive survey study by Oliveria et al 31 found that physicians do not treat hypertension more aggressively because they are willing to accept an elevated SBP in their patients. This has an important impact on public health because of the positive association between SBP and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…From the physicians' point of view, inappropriate or ineffective treatments, lack of acceptance or knowledge of hypertension treatment guidelines, costs and side-effects, and dosing schedules of drugs have been suggested to play a role in poor management [52,53,54]. As a result physicians have been shown to initiate treatment at higher BP thresholds than existing guidelines, are less attentive to controlling BP because they are satisfied with the existing BP, seldom intensify drug therapy for BP above target levels and are more likely to treat or control increased diastolic BP than systolic BP [53,54,55].…”
Section: Observational Studies On Hypertension Treatment and Controlmentioning
confidence: 99%
“…As a result physicians have been shown to initiate treatment at higher BP thresholds than existing guidelines, are less attentive to controlling BP because they are satisfied with the existing BP, seldom intensify drug therapy for BP above target levels and are more likely to treat or control increased diastolic BP than systolic BP [53,54,55].…”
Section: Observational Studies On Hypertension Treatment and Controlmentioning
confidence: 99%